2018
DOI: 10.3389/fimmu.2018.00166
|View full text |Cite
|
Sign up to set email alerts
|

The Neurokinin-1 Receptor Contributes to the Early Phase of Lipopolysaccharide-Induced Fever via Stimulation of Peripheral Cyclooxygenase-2 Protein Expression in Mice

Abstract: Neurokinin (NK) signaling is involved in various inflammatory processes. A common manifestation of systemic inflammation is fever, which is usually induced in animal models with the administration of bacterial lipopolysaccharide (LPS). A role for the NK1 receptor was shown in LPS-induced fever, but the underlying mechanisms of how the NK1 receptor contributes to febrile response, especially in the early phase, have remained unknown. We administered LPS (120 µg/kg, intraperitoneally) to mice with the Tacr1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…On the contrary, we found no difference in the febrigenic effect of prostaglandin (PG) E 2 administered into the brain between Tacr1 −/− and Tacr1 +/+ mice. At 40 minutes after LPS administration, serum concentrations of pyrogenic cytokines and COX-2 mRNA expression in the lungs, liver, and brain did not differ between the genotypes, whereas COX-2 protein expression was lower in the lungs and, to a lesser extent, in the liver of Tacr1 −/− mice than in their Tacr1 +/+ littermates [1]. These results show that the NK1 receptor is involved in fever genesis through the facilitation of COX-2 protein expression in peripheral LPS-processing organs such as the lungs and the liver (Figure 1).…”
Section: Front Matter: Discoverymentioning
confidence: 85%
See 4 more Smart Citations
“…On the contrary, we found no difference in the febrigenic effect of prostaglandin (PG) E 2 administered into the brain between Tacr1 −/− and Tacr1 +/+ mice. At 40 minutes after LPS administration, serum concentrations of pyrogenic cytokines and COX-2 mRNA expression in the lungs, liver, and brain did not differ between the genotypes, whereas COX-2 protein expression was lower in the lungs and, to a lesser extent, in the liver of Tacr1 −/− mice than in their Tacr1 +/+ littermates [1]. These results show that the NK1 receptor is involved in fever genesis through the facilitation of COX-2 protein expression in peripheral LPS-processing organs such as the lungs and the liver (Figure 1).…”
Section: Front Matter: Discoverymentioning
confidence: 85%
“…As discussed in the highlighted study [1], NK1 receptors are expressed in macrophages and granulocytes, and the SP-NK1 receptor pathway can trigger the activation and trafficking of these cells, as well as, the upregulation of COX-2 and the production of proinflammatory mediators. It is suggested that SP-induced activation of NK1 receptors on immune cells exacerbates systemic inflammation via recruitment of leukocytes and induction of inflammatory mediator expression [1,3]. Indeed, in septic and aseptic (LPS) animal models of systemic inflammation, the levels of SP were elevated in the lungs and the liver [3], i.e.…”
Section: Front Matter: Discoverymentioning
confidence: 94%
See 3 more Smart Citations